DIFFERENCES IN MEANING ENRICHMENT OF ASPECTUAL CONSTRUCTIONS IN ACCUSATIVE AND INSTRUMENTAL: ZAVRŠITI KUĆU OR ZAVRŠITI S KUĆOM (Philological Studies, 2019)
The paper examines the enriched compositionality (R. Jackendoff) of constructions with aspectual verb završiti (to finish) in different syntactic frames (završiti kuću and završiti s kućom) in Croatian. Experimental approach is used to explore the range of implicit predicates of sentences with male and female subjects. Analysis has shown that the implicit predicates in sentences with semantically incompatible constituents are the result of constructional meaning and the activation of the generalized event knowledge (K. McRae, M. Kazunaga) during sentence processing.
Keywords: aspectual verbs, završiti, accusative, instrumental, construction grammar, enriched compositionality, generalized event knowledge